Parenting Styles and Social Development in Early Childhood: Gaya Pengasuhan dan Perkembangan Sosial pada Masa Kanak-kanak Awal - Anik Rahayu Rahayu; Vanda Rezania Rezania (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Early childhood is a critical period in social development, during which family plays a central role in shaping children’s social behavior. Specific Background: Parenting styles represent one of the primary environmental factors influencing children’s social interaction, independence, and behavioral adjustment. Knowledge Gap: Although theoretical discussions on parenting styles are widely available, contextual empirical descriptions of how parental approaches relate to early childhood social development remain limited. Aims: This study aims to analyze the role of parenting styles in the social development of early childhood within the family environment. Results: The findings indicate that parenting patterns characterized by guidance, supervision, and emotional support are associated with positive social behaviors, including cooperation, empathy, and social responsibility. Conversely, less supportive parenting approaches correspond with weaker social adjustment. Novelty: This study provides a contextual qualitative analysis linking parenting patterns with observable social behaviors in early childhood. Implications: The results contribute to early childhood education and family education practices by emphasizing the importance of appropriate parenting strategies in supporting optimal social development. Keywords: Parenting Styles, Early Childhood Education, Social Development, Family Environment, Qualitative Research Key Findings Highlights; Parental guidance and supervision relate to cooperative behavior patterns. Emotional support corresponds with positive peer interaction. Inconsistent caregiving associates with limited social adjustment.